Divergent Axial Carpal Dislocation and Its Pathomechanics - López-Cervantes, R. E.; García-Elias, M.; Soto, I. Bermúdez (Journal of Wrist Surgery, 2018)
Background Axial carpal dislocations and fracture dislocations are 1.4 to 2.08% of all the fractures and dislocations of the wrist. These injuries are caused by high-energy blast or compression mechanisms. Only 11 cases of axial–radial–ulnar (ARU) fracture dislocations have been described in the literature.Case Description We describe a case with a traumatic transtrapezoid, peritrapezium, transhamate, peripisiform ARU in a patient with acute compartment syndrome, traumatic transverse flexor retinaculum (TFR) rupture, and radial nerve palsy.Literature Review The ARU fractures are injuries where the carpus is torn into three columns. ARU injuries have a high incidence of neurovascular, soft-tissue cover, and muscular-associated injuries. Depending on the injuries mentioned earlier, a bad functional prognosis can be expected. Nearly without exception, in ARU cases, a traumatic TFR rupture takes place. Garcia-Elias mentioned that the injury pattern is given by the speed, magnitude, and energy entry point.Clinical Relevance We describe a case of an ARU injury which has not been previously described. In an analysis of the 12 ARU cases previously reported, we observed that when two or more applied forces converge, an ARU injury pattern can occur. That suggests that in ARU injuries, one side of the injury occurs before the other. Due to the extensive carpal damage, in patients with ARU, a restricted range of motion is more likely to happen than residual instability. Thus, in all these cases, an early mobilization and intensive rehabilitation is highly necessary.
Keywords: carpal bones; dislocations; carpal joints; compression mechanisms; high-energy trauma